Analisis Hasil Reses DPRD dalam Penyusunan Dan Penetapan APBD Kabupaten Ogan Komering Ulu Selatan Tahun Anggaran 2014 - Alva Beriansyah; Dyah Mutiarin (Universitas Muhammadiyah Yogyakarta, 2015)
The Parliament recess activity is a form of participation from the community in the planning process of developmentin the area. Perliament of the South OKU regency implement recess 3 times in one year. The process of recessactivities began with preparations of parliament to determine the place, time and all material to be delivered duringrecess implementations. Preparations of recess participants conducted to determine the aspirations to be deliveredduring recess. The aspiration to be delivered during the recess comes from Musrembangdes, all aspirations has beendelivered during the previous recess and unrealized aspirations, also in village meeting. The first thing that discussedto the implementation of the recess is consulting parliament activities before and after recess. The second things arethe expressions of aspirations by recess participant. Aspirations articulated by recess participants will be identifiedtogether by the recess participants and parliament. The results of this agenda will be used as a report aspirationsrecess and it will be submitted to the regional government. Articulate of aspirations during the discussions of KUA andPPAS will be prepared at fractions meeting by asking the opinions of each member in factions by the discussions of thegeneral statements of fractions. The general statement form fraction used as a reference for members of parliamentsto follow commission and board budget meeting